Metadata standards and practical guidelines for specimen and DNA curation when building barcode reference libraries for aquatic life - Frédéric Rimet (Pensoft Publishers, 2021)
DNA barcoding and metabarcoding is increasingly used to effectively and precisely assess and monitor biodiversity in aquatic ecosystems. As these methods rely on data availability and quality of barcode reference libraries, it is important to develop and follow best practices to ensure optimal quality and traceability of the metadata associated with the reference barcodes used for identification. Sufficient metadata, as well as vouchers, corresponding to each reference barcode must be available to ensure reliable barcode library curation and, thereby, provide trustworthy baselines for downstream molecular species identification. This document (1) specifies the data and metadata required to ensure the relevance, the accessibility and traceability of DNA barcodes and (2) specifies the recommendations for DNA harvesting and for the storage of both voucher specimens/samples and barcode data.